Role of uric acid in neurodegenerative diseases, focusing on Alzheimer and Parkinson disease: A new perspective - Mohammed Alrouji; Hayder M. Al‐kuraishy; Ali I. Al‐Gareeb; Mohammed S. Alshammari; Athanasios Alexiou; Marios Papadakis; Mostafa M. Bahaa; Gaber El‐Saber Batiha (Wiley, 2024)
Abstract Neurodegenerative diseases (NDs) such as Alzheimer disease (AD) and Parkinson disease (PD) are group of diseases affecting the central nervous system (CNS) characterized by progressive neurodegenerations and cognitive impairment. Findings from different studies highlighted the beneficial and detrimental effects of serum uric acid on the development and progression of NDs. Therefore, this mini‐review aims to discuss the beneficial and detrimental effects of uric on NDs. The neuroprotective effect of uric acid is mainly related to the antioxidant effect of uric acid which alleviates oxidative stress‐induced neurodegeneration in AD and PD. However, long‐term effect of hyperuricemia prompts for the development and progression of cognitive impairment. Hyperuricemia is associated with cognitive impairment and dementia, and gout increases dementia risk. In addition, hyperuricemia can cause cerebral vascular injury which is a risk factor for vascular dementia and cognitive impairment. Taken together, the relationship between uric acid and NDs risk remains conflicting. Hence, preclinical and clinical studies are indicated in this regard.